Niosomal Nanovesicular Spray Systems for Topical Drug Delivery: Formulation Strategies, Characterization, and Therapeutic Applications - Shaikh Zoya Fatema,; Vaidya Vijay D,; Borkar Shilpa S,; Baheti Jagdish, (Asian Journal of Pharmaceutical Research and Development, 2026)
Topical drug delivery is commonly used for localized therapy, but conventional gels, creams, and ointments often face limitations in skin penetration and consistent therapeutic response. Niosome-based nanosprays provide an advanced alternative by encapsulating both hydrophilic and lipophilic drugs in non-ionic surfactant vesicles with a bilayer structure. Key formulation factors affecting performance include surfactant type, cholesterol content, vesicle size and surface properties, and drying methods. Converting liquid dispersions into dry nanospray powders enhances stability, handling, and storage while preserving vesicle integrity. Preclinical studies show that niosomalnanosprays penetrate deeper skin layers, extend dermal retention, and improve therapeutic outcomes for dermatological and inflammatory conditions compared with traditional topical systems. Despite these advantages, challenges remain in scaling up production, ensuring long-term stability, and validating clinical efficacy. Employing quality-by-design strategies and optimizing formulations are essential for translating niosome-based nanosprays into commercially viable and effective therapeutic products.